Chemical nature and sources of fine particles in urban Beijing: Seasonality and formation mechanisms. (July 2020) - Gu, Yifang; Huang, Ru-Jin; Li, Yongjie; Duan, Jing; Chen, Qi; Hu, Weiwei; Zheng, Yan; Lin, Chunshui; Ni, Haiyan; Dai, Wenting; Cao, Junji; Liu, Quan; et al.
Highlights: Nitrate contribution overwhelms sulfate. Secondary formation dominates in OA in all seasons. The formation mechanisms of SOA differ in different seasons. Highly oxidized organic aerosol dominates in SOA irrespective of the pollution level. Abstract: To mitigate air pollution in China, a legislative 'Air Pollution Prevention and Control Action Plan' has been implemented by the Chinese government since 2013. There is, however, a lack of investigations for long-term trends in the composition, sources and evolution processes of PM1 (particulate matter with diameter less than 1 μm) after the implementation. To evaluate the effectiveness of these control measures, we present a year-long real-time measurement of the chemical composition of PM1 at an urban site in Beijing from November 2014 to November 2015, and the results are compared with previous studies from 2008 to 2013 to gain insights into the variations of the chemical composition and sources of PM1 in Beijing. Large seasonal differences were observed in the mass concentrations of PM1 species and general declining trend was observed in the last seven years. Specifically, the annual averages of mass concentrations in 2014–2015 decrease by 16–43% (PM1 ), 23–43% (organic aerosol, OA), 38–68% (sulfate), 26–51% (nitrate), 18–33% (ammonium) and 27–38% (chloride) compared to those from 2008 to 2013. During winter and summer, the seasonal mass concentrations of sulfate and nitrate show more significant declines especially in summer 2008 (79% and 81%) and summer 2011 (76% and 77%). The nitrate-to-sulfate ratio is higher in 2014–2015 (1.5 ± 0.6) than that in 2013 (1.0 ± 0.3), largely due to significant reduction in SO2 emissions, suggesting that nitrate is becoming more important than sulfate in particulate pollution in Beijing. OA is the dominant PM1 fraction (>45%) in all seasons and the mass concentrations/contributions of both primary and secondary OA show different seasonality. As for the more oxidized oxygenated OA (MO-OOA) and less oxidized oxygenated OA (LO-OOA), the contributions of MO-OOA are much higher than those of LO-OOA (27–62% vs. 6–26%) in both high-pollution and low-pollution days. Aqueous-phase processes are found to facilitate the formation of MO-OOA while photochemical oxidation formation is a major contributor of LO-OOA in winter, and photochemical oxidation plays a major role in the formation of MO-OOA in summer and fall. The current study provides a comprehensive seasonal comparison of chemical composition and formation of PM1 in Beijing and a pacesetter in tackling PM pollution for other equally polluted megacities, after implementation of more stringent control measures after 2013.